Behavioral archaeology : principles and practice - Schiffer, Michael B. (Michael Brian), 1947-
Behavioral archaeology offers a way of examining the past by highlighting human engagement with the material culture of the time. Behavioral Archaeology: Principles and Practice, offers a broad overview of the methods and theories used in this approach to archaeology. Opening with an overview of the history and key concepts, the book goes on to systematically cover both principles and practice: the philosophy of science and the scientific method; artifacts and human behavior; archaeological inference; formation processes of the archaeological record; technological change; behavioral change; and ritual and religion. Detailed case studies show the relevance of behavioral method and theory to the wider field of archaeological studies. The book will be invaluable to students of archaeology and anthropology.